1998
DOI: 10.2165/00002018-199819040-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-Benefit Assessment of Pharmacotherapy for Anxiety Disorders in Children and Adolescents

Abstract: Few pharmacotherapy trials have been undertaken in young people with anxiety disorders. Of those conducted, few are placebo-controlled or blinded, and often sample size is small, making interpretation of the data difficult. Case report and uncontrolled trial data generally support the efficacy of pharmacotherapy in many of the anxiety disorders seen in young people. However, most attempts to confirm these impressions in controlled trials have not been as encouraging. Further controlled studies in larger, diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…The database of medication trials for pediatric anxiety disorders is smaller than for adults [25]; nevertheless, SSRIs are approved for childhood OCD, and an important recent trial reported efficacy of fluvoxamine in a placebo-controlled trial of patients with GAD, separation anxiety, or SAD [26]. Nevertheless, in order to ensure optimal evaluation and integrated treatment, referral to a specialist may be needed.…”
Section: Younger and Older Patientsmentioning
confidence: 99%
“…The database of medication trials for pediatric anxiety disorders is smaller than for adults [25]; nevertheless, SSRIs are approved for childhood OCD, and an important recent trial reported efficacy of fluvoxamine in a placebo-controlled trial of patients with GAD, separation anxiety, or SAD [26]. Nevertheless, in order to ensure optimal evaluation and integrated treatment, referral to a specialist may be needed.…”
Section: Younger and Older Patientsmentioning
confidence: 99%
“…Mood and environment may also contribute, as may the presence of neurological disorders, being young (Litchfield, 1980;Hawkridge & Stein, 1998) or over 65 or having a learning disability or CNS degenerative disease (Bond, 1998). Perhaps the single most important factor is underlying personality, as those with a history of aggression and poor impulse control may be more prone to experiencing paradoxical reactions to benzodiazepines.…”
Section: Who Is Most At Risk?mentioning
confidence: 99%
“…[1] In addition to the persistence of original symptoms into adulthood, additional comorbid disorders, such as major depression (which can increase the risk of a suicide attempt 2-to 6-fold [4] ), may develop with time. [2,4,5] Higher rates of alcohol dependence, substance abuse and cigarette smoking are also associated with anxiety disorders. [4] Furthermore, social dysfunction may result from the failure to diagnose and treat anxiety disorders during adolescence, a period when individuals acquire social skills that facilitate the transition to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, anxiety disorders can have an important impact on society through increased financial dependence on the welfare system and higher rates of use of medical and mental health services. [5] Although there are few well controlled trials evaluating the efficacy of pharmacological agents in the treatment of anxiety disorders in paediatric patients, selective serotonin (5-hydroxytryptamine) reuptake inhibitors (SSRIs), tricyclic antidepressants (TCAs), [2] benzodiazepines, buspirone and β-blockers have been used in this population. cognitive-behavioural therapy) options, or a combination of the two approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation